2009
DOI: 10.1186/1472-6939-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices survey on organ donation among a selected adult population of Pakistan

Abstract: Background: To determine the knowledge, attitudes and practices regarding organ donation in a selected adult population in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
126
7
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 17 publications
30
126
7
12
Order By: Relevance
“…This deficiency which was observed among general public, students, and health professionals may be due to the lack of information and difficulty in understanding the legal terminologies. As was observed, mass media could be the best choice to convey the message, so that individuals could understand their roles and responsibilities with regards to organ donations [1,2,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This deficiency which was observed among general public, students, and health professionals may be due to the lack of information and difficulty in understanding the legal terminologies. As was observed, mass media could be the best choice to convey the message, so that individuals could understand their roles and responsibilities with regards to organ donations [1,2,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been legalized in India, under the "Transplantation of Organ Act, 1994". Globally, the prevalence of knowledge on organ donation was found to range from 60% to 85%, on using different knowledge variables [2]. Medical students have different opinions which are governed by socio cultural factors such as traditional customs, the practice of preservation of intact body after death, uneasiness in discussing death related issues and family objections.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the findings of our study, Sucharita et al, Saleem et al, Khan et al and Alghanim have found media (Television) as the major source of information among study participants. 6,9,19,20 Regarding attitude of study participants towards organ donation in our study, 76% of the participants responded that they would donate their organs if needed and 66% even agreed to donate organs from their family members after brainstem death. Similar findings regarding favorable attitude of participants towards organ donation were reported across the globe in various studies by Sucharita et al, Marques-Lespier et al, Satish et al, Alsaied et al, Alghanim and Ahlawat et al 6,12,15,16,20,21 These observations were different from the study done in Nigeria by Odusanya where only 30% were willing for organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Taimur et al stated that doctors can be used as efficient sources of information, to generate a favorable attitude towards organ donation amongst the population. 9 Medical students being the future doctors of the country, they should have a positive attitude and high level of knowledge which can create a positive environment and promote organ donation. Hence, this study was undertaken to assess their knowledge and attitudes regarding organ donation which will help to identify the gaps and provide training on organ donation.…”
Section: Introductionmentioning
confidence: 99%
“…Higher education, younger age and factors associated with political affiliation determined respondents' willingness to donate organs, and consent was given to donors' relatives (Saleem et al, 2009). …”
Section: Introductionmentioning
confidence: 99%